ARKEOLOGI MAKNA TOPENG: ANALISIS SEMIOTIS FOTO KOMPAS “MENYAMBUT PESTA DEMOKRASI” - Fabianus Fensi (Program studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Persada Indonesia YAI, 2021)
The reaction of the market community of Gede, Solo, Central Java, to the declaration of Joko Widodo-Kiai Ma'ruf Amin and Prabowo Subianto-Sandiaga Salahudin Uno, as candidates for President and Vice President, unique. They wear four candidates' masks. This research aims to explore the meaning of the using of mask. Using Michel Foucault's hermeneutical-archeological approach, it is hoped that traces of the deepest meaning can be traced, why do people use masks? Charles Sanders Peirce's semiotic analysis with triangle meaning method (representament, object, and interpretant) is used to data analyze, especially mask photos. As one type of qualitative research, this study produces meaning findings as follows: real markets characterized by crowds, crowded people, passing sellers and buyers, and the transportation activities of busy goods also do not occur. This condition symbolizes criticism of the behavior of the government which is too happy to play the image in front of their people. This is also a symbol of weakness or failure of the government to place the people (in the market) as the main actors driving the welfare of a nation. We all know that the welfare of a nation is represented by the high activity of